Characterization and Digestibility of Detoxified Castor Oil Meal for Japanese Quails - Santos, Pa Dos; Ludke, Mcmm; Ludke, Jv; Rabello, Cbv; Santos, Mjb Dos [UNESP]; Torres, Tr (Fundação APINCO de Ciência e Tecnologia Avícolas, 2015)
These experiments were performed to determine the chemical composition, coefficients of nutrient and energy metabolizability, amino acid composition, and cytotoxicity of different castor oil meals subjected to different detoxification processes and added to the diet of Japanese quails. In the trial, 180 46-d-old female Japanese quails were distributed according to a completely randomized design into five treatments and with replicates of six bird each. The treatments consisted of following detoxification methods of castor oil meal: Castor oil meal A (CMA) - recovery in alcohol at 80 °C for 20 minutes and drying at 80 °C; castor oil meal B (CMB) and C (CMC) - recovery in alcohol at 80 °C for 6 minutes, neutralization with 5% NaOH, and drying under direct sunlight sun for two days (CMB) or pelleted (CMC); castor oil meal D (CMD) - recovery in alcohol at 110 °C for 15 minutes and drying at 110 °C. Castor oil meal was added replacing 20% of the reference diet. There was slight chemical composition variation (1.21% in crude protein, 6% in dry matter, 2.2% in ether extract and 64 kcal/kg in gross energy) among the castor oil meals submitted to the different treatments. The castor oil meal submitted to treatment C showed the highest amino acid values. In the cytotoxicity test, treatment D presented lower ricin activity. Castor oil meals A, C, and D may be included in Japanese quail diets; however, castor oil meal D is recommended due to the simplicity its industrial process, its low toxicity, and metabolizability coefficients obtained.
Keywords: Alternative food; poultry; cytotoxicity; digestibility; energy